Dalit Literature and Political Consciousness in Sharad Poudel’s Likhe - Charmakar, Rudra Bahadur (Patan Gyansagar, 2024)
The article attempts to explore the class and caste consciousness in Nepali Dalit literature; and, to identify contemporary Dalit literature and its presentation of subject matters, social messages and themes. The article sketches how Dalit literature reflects the contemporary socio-political and economic issues where Dalit community is routinely discriminated, exploited, boycotted, and excluded in various social spheres. Basically, every social structure has binary oppositions such as masters-slave, landlord-worker, bourgeois-proletariat and 'haves' and 'haves not'. Dalit literature is a medium to fight against the system for rights, equality and social dignity. The article employs the concept of Marxist concept of class consciousness and aesthetic on Poudel’s novel Likhe. The paper adopts the analytical and exploratory method and qualitative approach as a research tool.